2006
DOI: 10.1002/nbm.1038
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transferrin receptor and ferritin following ferumoxides–protamine sulfate labeling of cells: implications for cellular magnetic resonance imaging

Abstract: Ferumoxides-protamine sulfate (FE-Pro) complexes are used for intracellular magnetic labeling of cells to non-invasively monitor cell trafficking by in vivo MRI. FE-Pro labeling is non-toxic to cells; however, the effects of FE-Pro labeling on cellular expression of transferrin receptor (TfR-1) and ferritin, proteins involved in iron transport and storage, has not been reported. FE-Pro-labeled human mesenchymal stem cells (MSCs), HeLa cells and primary macrophages were cultured from 1 week to 2 months and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 36 publications
10
103
2
Order By: Relevance
“…Long term incubation up to 72 hours has also been investigated and shows no adverse effect upon mesenchymal stem cells . Similar results are found on ferumoxide-polylysine and ferumoxides-protamine sulfate complex toward mesenchymal stem cells (Arbab et al, 2003;Pawelczyk et al, 2006).…”
Section: Impact Of Magnetic Nanoparticles In Stem Cellsupporting
confidence: 77%
“…Long term incubation up to 72 hours has also been investigated and shows no adverse effect upon mesenchymal stem cells . Similar results are found on ferumoxide-polylysine and ferumoxides-protamine sulfate complex toward mesenchymal stem cells (Arbab et al, 2003;Pawelczyk et al, 2006).…”
Section: Impact Of Magnetic Nanoparticles In Stem Cellsupporting
confidence: 77%
“…Bulte et al(10) used CD71 as a vehicle for intracellular monocrystalline iron oxide nanoparticle delivery in oligodendrocyte progenitor cells. Pawelczyk et al (33) found that Fe-Pro complex in vitro labeling resulted in a transient decrease in CD71 mRNA and protein levels of both HeLa and human mesenchymal stem cells. In contrast, in vitro Fe-Pro complex labeling of primary macrophages resulted in an increase in CD71 mRNA but not in protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that accumula- tion of ROS-generating substances (ATDR, iron-containing nanoparticles) by cells caused oxidation of these residues, formation of disulfide bonds and resulted in disturbances in protein conformation and interaction with mRNA causing increase of TFR1 expression [33]. Such phenomenon of sinchronous changes in FTH and TFR1 expression as a result of oxidative stress was observed by different groups of scientists on different cell lines [34,35].…”
Section: Discussionmentioning
confidence: 99%